Laboratory model to evaluate efficacy of an experimental titanium oxide nanofibers bleaching agent - Clayton Tran; Ellin Choi; Brittany Watu; Udochukwu Oyoyo; Christopher Perry; So Ran Kwon (Restorative Dentistry & Endodontics, 2021)
ObjectivesThis study aimed to use a laboratory model to evaluate the efficacy of an experimental bleaching agent.Materials and MethodsThe model used human extracted molars that were treated and measured for bleaching efficacy. Teeth (n = 50) were distributed into 5 groups: Negative control (NC): immersion in water for 8 hours; Nanofibers (NFs): Experimental titanium dioxide nanofibers with stirring and light activation for 8 hours; Whitestrips (WS): Crest 3D White Glamorous White Whitestrips, 2 applications daily for 30 minutes, 14 days; 1% hydrogen peroxide (HP) standard: 1% hydrogen peroxide for 8 hours; and 30% HP standard: 30% hydrogen peroxide for 8 hours. Instrumental measurements were performed using a spectrophotometer. Results were recorded at baseline, 1-day post-bleaching, and 1-week post-bleaching. Kruskal-Wallis procedure was used to determine differences in color change. Pearson correlation was used to evaluate the relationship between visual and instrumental measurements. Tests of hypotheses were 2-sided with alpha = 0.05.ResultsThere was no significant difference in color parameters (L1, a1, b1, and shade guide units [SGU]) at baseline (p > 0.05). There was a significant difference among the groups for overall color change (ΔE*ab) and change in shade guide units (ΔSGU) at 1-day and 1-week post-bleaching (p < 0.05). The higher the HP concentration, the higher the color change as expressed in ΔSGU and ΔE*ab. The negative control exceeded the perceptibility threshold of ΔE* = 1.2 regardless of time point. NFs showed a decrease in chroma, but were not statistically different compared to the negative control.ConclusionsThe laboratory model was successful in screening an experimental bleaching agent.